Energy efficiency lighting system for a Kolej Kemahiran Tinggi Mara Ledang (KKTM Ledang) - Mohd Asmadee, Nurul Syafiqah; Ming, Foong Lee; Zakaria, Normah (2020)
Energy efficiency and energy saving are global attempts to solve the problem of global warming in order to achieve the objective of a sustainable future. Educational institutions are one of the contributors to energy consumption, especially hands-on training given by vocational colleges. This analysis was therefore carried out to examine the use of electricity in a college and to concentrate on the lighting system, with a view to proposing a college lighting system for energy efficiency by referring to the specifications of the Malaysian Energy Commission for MS ISO 8995 and MS 825. The return on investment of the lighting system developed was also determined.